Antiferromagnetic domain wall as spin wave polarizer and retarder - Jin Lan (Nature Portfolio, 2017)
Spin waves are promising candidates as carriers for energy-efficient information processing, but they have not yet been fully explored application wise. Here the authors theoretically demonstrate that antiferromagnetic domain walls are naturally spin wave polarizers and retarders, two key components of magnonic devices.